2016
DOI: 10.1021/acs.jpca.5b09004
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopentadienone Oxidation Reaction Kinetics and Thermochemistry for the Alcohols, Hydroperoxides, and Vinylic, Alkoxy, and Alkylperoxy Radicals

Abstract: Cyclopentadienone has one carbonyl and two olefin groups resulting in 4n + 2 π-electrons in a cyclic five-membered ring structure. Thermochemical and kinetic parameters for the initial reactions of cyclopentadienone radicals with O2 and the thermochemical properties for cyclopentadienone-hydroperoxides, alcohols, and alkenyl, alkoxy, and peroxy radicals were determined by use of computational chemistry. The CBS-QB3 composite and B3LYP density functional theory methods were used to determine the enthalpies of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…The difference in IDT predictions at 900 K is about an order of magnitude. Using the higher entropy value from the QC calculations, the equilibrium shifts to form this radical which promotes reactivity, resulting in shorter predicted IDTs and Sebbar et al 20 10 hydroxycyclohexadienyl peroxy isomers Chen et al 21 11 C 1 −C 4 hydroperoxides and peroxy radicals Wang et al 22 12 alcohols, hydroperoxides, and vinylic, alkoxy, and alkylperoxy radicals Yommee et al 23 13 hydroxyl-and hydroperoxide-substituted furan, methylfuran, and methoxyfuran Hudzik et al 24 14 isooctane and carbon radicals Snitsiriwat et al 25 better agreement with the experimental data. Further investigation found that, using the GA method, there are two different ways in which the thermochemistry of 2-propenyl-1methyl radical can be calculated, as shown in Figure 4 and Table 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in IDT predictions at 900 K is about an order of magnitude. Using the higher entropy value from the QC calculations, the equilibrium shifts to form this radical which promotes reactivity, resulting in shorter predicted IDTs and Sebbar et al 20 10 hydroxycyclohexadienyl peroxy isomers Chen et al 21 11 C 1 −C 4 hydroperoxides and peroxy radicals Wang et al 22 12 alcohols, hydroperoxides, and vinylic, alkoxy, and alkylperoxy radicals Yommee et al 23 13 hydroxyl-and hydroperoxide-substituted furan, methylfuran, and methoxyfuran Hudzik et al 24 14 isooctane and carbon radicals Snitsiriwat et al 25 better agreement with the experimental data. Further investigation found that, using the GA method, there are two different ways in which the thermochemistry of 2-propenyl-1methyl radical can be calculated, as shown in Figure 4 and Table 2.…”
Section: Introductionmentioning
confidence: 99%
“…Ritter and Bozzelli developed THERM (THermo Estimation for Radicals and Molecules) based on Benson’s GA method, which can be used as illustrated in Figure . Bozzelli and co-workers have also studied the thermochemistry of different classes of species including sulfurated, nitridated, fluorinated, oxygenated, and saturated hydrocarbons, Table . Enthalpies of formation, entropies, and heat capacities have been compiled for certain classes of species using density functional theory (DFT) and composite compound methods, from which bond dissociation energies (BDEs) of similar type of bonds and GAVs were systematically reported and compared.…”
Section: Introductionmentioning
confidence: 99%
“…where h p is the Planck's constant and к b is Boltzmann's constant, R is gas constant, and R = 1.987 cal mol −1 K −1 . 34,38,49,50 The high-pressure limit rate constant parameters are calculated based on the thermochemical properties of reactant, product, and transition state geometries optimized under the CBS-QB3 level. Temperature-and pressure-dependent rate constants are calculated using the multichannel, multifrequency quantum Rice-Ramsperger-Kassel (QRRK) analysis for k(E) based on a master equation analysis for falloff and stabilization as implemented in the CHEMASTER code.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…The entropy differences between the reactants and the transition states (Δ S ≠ ) over the temperature range of 200–3000 K were used to determine the preexponential factor ( A , s −1 or cm 3 mol −1 s −1 ). The preexponential values of A are expressed by AT=κbT/hpexpΔS/Rwhere h p is the Planck's constant and к b is Boltzmann's constant, R is gas constant, and R = 1.987 cal mol −1 K −1 …”
Section: Calculation Methodsmentioning
confidence: 99%
“…In addition, it can be burdensome to consistently include the multidimensional tunneling effect and/or anharmonicity effects on rate constants in conventional RRKM calculations. A simpler method is the quantum Rice-Ramsperger-Kassel (QRRK) approximation combined with chemical activation theory, as developed in modern form by Dean and improved further by Dean and Bozzelli and their co-workers, which uses kinetic parameters estimated empirically or obtained from the high-pressure results of canonical-ensemble transition-state theory calculations combined with electronic structure calculations to predict the pressure effect on the dissociation rate. These workers usually used CBS-QB3 theory for the electronic structure calculations.…”
Section: Introductionmentioning
confidence: 99%